Teachers’ use of open questions: investigating the various functions of open questions as a mediating tool in early literacy education - Ingvill Krogstad Svanes (Taylor & Francis Group, 2021)
This study identifies the various functions of open questions in whole-class teaching in language arts classrooms in primary school, and it explores how these questions may work as a mediating tool. Open questions are considered a valuable tool in classroom discourse, enhancing dialogue and students’ learning by giving the students an opportunity to elaborate on their thoughts. The analysis draws on two data sets and includes observations from four schools and an examination of whole-class teaching in 32 language arts lessons. The results show that the teacher practice of asking open questions has one core function – classroom management. The teachers also ask open questions that are more subject specific, and the material covers writing activities and orthography and grammar instruction. The functions of open questions are quite similar in the two data sets. This may indicate that the teachers’ open questions mediate an understanding of school culture and the values of the subject to the students, here how writing activities and grammar instruction should be interpreted. This article argues that we should go further than merely differentiating between open and closed questions and investigate the functions of open questions in the classroom.